Study of wear on anodised PM Aluminium Matrix composite reinforced with 15 wt % Saffil Alumina Short Fibre - Mohd Nazree, Derman (Universiti Malaysia Perlis, 2009)
Organized by School of Environmental Engineering, School of Materials Engineering and School of Bioprocess Engineering (UniMAP), 9th - 11th June 2007 at Park Royal Hotel, Penang.